Studying Technology Adoption Inhibition in the Context of Food Ordering Apps - Iyer, Easwar Krishna; Gujral, Anchit; Raundal, Anuja; Saxena, Hardik (Ushus Journal of Business Management, 2021)
Food ordering apps are dramatically changing the out-of-home food consumption. With mobile phones emerging as the ubiquitous self-help device, a new wave of food ordering is evolving. This study aims at identifying the technology adoption inhibitors that consumers face when they migrate from dine-out experience to online take-home experience. We propose insecurity, discomfort, infrastructure and inertia as four inhibitors for a full-scale migration to online food ordering and establish that all four variables are significant in explaining the current consumer inhibition in the area of the study mentioned. While adoption, acceptance and readiness for technology usage are given attention and focus, this study stands out as an analysis of consumer inhibition patterns.